Safety and immunogenicity of a novel 10-valent pneumococcal conjugate vaccine candidate in adults, toddlers, and infants in The Gambia—Results of a phase 1/2 randomized, double-blinded, controlled trial. Issue 2 (10th January 2020) - Clarke, Ed; Bashorun, Adedapo O.; Okoye, Michael; Umesi, Ama; Badjie Hydara, Mariama; Adigweme, Ikechukwu; Dhere, Rajeev; Sethna, Vistasp; Kampmann, Beate; Goldblatt, David; Tate, Andi; Weiner, Debra H; et al.
Highlights: Safe, effective and more affordable pneumococcal conjugate vaccines (PCV) are needed. This new PCV targets serotypes most likely to cause disease in low- and middle-income countries. The vaccine was safe and immunogenic in adults, toddlers and infants in this phase 1/2 trial. The data support progression to a phase 3 licensure trial of the new PCV. Abstract: Background: A more affordable pneumococcal conjugate vaccine (PCV) that provides comparable protection to current PCVs is needed to ensure sustainable access in resource-limited settings. Serum Institute of India Pvt. Ltd.'s PCV candidate (SIIPL-PCV) has the potential to meet this need as manufacturing efficiency has been optimized and the vaccine targets the most prevalent disease-causing serotypes in Africa and Asia. We report SIIPL-PCV's safety, tolerability, and immunogenicity in adults, toddlers, and infants in The Gambia. Methods: This phase 1/2, randomized, double-blind trial sequentially enrolled 34 PCV-naive adults (18–40 years old), 112 PCV (Prevenar 13® [PCV13])-primed toddlers (12–15 months old), and 200 PCV-naive infants (6–8 weeks old), who were randomized (1:1) to receive SIIPL-PCV or a licensed comparator vaccine. Infants received three-doses of SIIPL-PCV or PCV13 at 6, 10, and 14 weeks of age co-administered with routine Expanded Program on Immunization (EPI) vaccines. Reactogenicity was solicited through seven-days post-vaccination; unsolicited adverse events (AEs) were assessed throughout the study. The safety and immunogenicity of a matching booster at 10–14 months of age were evaluated in a subset of 96 infants. Immune responses were evaluated post-primary and pre- and post-booster vaccinations. Results: Reactogenicity was primarily mild-to-moderate in severity. In infants, the most common solicited reactions were injection-site tenderness and fever, with no meaningful treatment-group differences. There were no serious or severe vaccine-related AEs and no meaningful trends in SAEs, vaccine-related AEs, or overall AEs. Infant post-primary seroresponse rates (IgG level ≥ 0.35 µg/mL) were ≥89% for all serotypes except 6A (79%) in the SIIPL-PCV group. IgG GMCs were >1 µg/mL for all serotypes in both SIIPL-PCV and PCV13 groups. Post-booster GMCs were comparable between groups. Conclusion: SIIPL-PCV was well-tolerated, had an acceptable safety profile, and was immunogenic for all vaccine serotypes. Results support the evaluation of SIIPL-PCV in a phase 3 non-inferiority trial. Clinicaltrials.gov: NCT02308540 .